A regularity criterion of strong solutions to the 2D compressible magnetohydrodynamic equations. (October 2016) - Wang, Teng
Abstract: This paper establishes a regularity criterion of strong solutions to the two-dimensional compressible magnetohydrodynamic (MHD) flows. The criterion depends on the density, but is independent of the velocity and the magnetic field. More precisely, once the strong solutions blow up, the L ∞ -norm for the density tends to infinity. In particular, the vacuum in the solutions is allowed.